Gluconeogenesis in Leishmania mexicana: CONTRIBUTION OF GLYCEROL KINASE, PHOSPHOENOLPYRUVATE CARBOXYKINASE, AND PYRUVATE PHOSPHATE DIKINASE - Rodriguez-Contreras, Dayana (J Biol Chem, 2014)
Gluconeogenesis is an active pathway in Leishmania amastigotes and is essential for their survival within the mammalian cells. However, our knowledge about this pathway in trypanosomatids is very limited. We investigated the role of glycerol kinase (GK), phosphoenolpyruvate carboxykinase (PEPCK), and pyruvate phosphate dikinase (PPDK) in gluconeogenesis by generating the respective Leishmania mexicana Δgk, Δpepck, and Δppdk null mutants. Our results demonstrated that indeed GK, PEPCK, and PPDK are key players in the gluconeogenesis pathway in Leishmania, although stage-specific differences in their contribution to this pathway were found. GK participates in the entry of glycerol in promastigotes and amastigotes; PEPCK participates in the entry of aspartate in promastigotes, and PPDK is involved in the entry of alanine in amastigotes. Furthermore, the majority of alanine enters into the pathway via decarboxylation of pyruvate in promastigotes, whereas pathway redundancy is suggested for the entry of aspartate in amastigotes. Interestingly, we also found that l-lactate, an abundant glucogenic precursor in mammals, was used by Leishmania amastigotes to synthesize mannogen, entering the pathway through PPDK. On the basis of these new results, we propose a revision in the current model of gluconeogenesis in Leishmania, emphasizing the differences between amastigotes and promastigotes. This work underlines the importance of studying the trypanosomatid intracellular life cycle stages to gain a better understanding of the pathologies caused in humans.